Utilización de 4 saborizantes en la dieta de cerdos landrace durante la etapa de crecimiento - engorde en la granja experimental de la Universidad Estatal de Bolívar - Ramos Vacacela, Alexandra Paola (2019)
This thesis made an evaluation of 4 flavorings in the diet of Landrace pigs during the growth and fattening stage, so we proposed to establish the best flavoring in the feeding of Landrace pigs in the growth-fattening stage, to evaluate the gain of Weight in each of the treatments, determine which treatment obtained better performance and palatability and finally determine the economic benefit / cost ratio. For this investigation, the experimental design that was choosen was a completely randomized blocks design (DBCA) with 5 treatments and 5 repetitions, with a total of 25 experimental units, Landrace pigs of 2 months of age with an initial average weight of 11 kg. The experimental results showed significant statistical differences during the growth and fattening stage, where it was observed that at least one of the flavorings had significant effects throughout the investigation. Based on the results, we can recommend the treatment that obtained the best performance and palatability treatment 5; the pigs arrived at the establishment with an average weight of 11 kg, after completing the growth and fattening stages they reached an ideal final weight for the T5 treatment with the commercial balanced mixture plus Flavit BANANO flavoring, where it reached a final weight of 69.6 kg and next to it the alimentary conversion of 1.72 kg is manifested in the growth stage and in the fattening stage a feed conversion of 3.6 kg is found. Regarding the benefit-cost ratio, it is concluded that the T5 treatment with Flavit BANANO flavoring addition obtained a better cost benefit index during this investigation, which should take into account that in this treatment the price for which they were sold was higher, therefore the cost benefit will be higher, unlike the other treatments in which the sale price was lower, with a net gain of $ 0.46.